Pediatric Dialysis Case Studies : A Practical Guide to Patient Care - Warady, Bradley A.; Schaefer, Franz; Alexander, Steven R. (Springer International Publishing : Imprint: Springer, 2017)
Edited by the same team that developed the successful Pediatric Dialysis and its second edition, this text features clinical management principles that are integral to the care of children receiving chronic dialysis. Each chapter is introduced by a case presentation that serves as the basis for key learning points that are clinically applicable and presented in a succinct manner. The topics included in Pediatric Dialysis Case Studies cover virtually all aspects of pediatric dialysis care and represent the efforts of an international group of experts with firsthand clinical expertise from all disciplines represented in the pediatric dialysis team. This resource is certain to help the clinician achieve improved outcomes for these often complex patients.
Keywords: Medicine.; General practice (Medicine).; Nephrology.; Pediatrics.; elektronické knihy; electronic books